An Exploerer's Guide: The Shenandoah Valley & Mountains of the Virginias - Hargan, Jim (The Countryman Press, 2005)
A lively, comprehensive guide to the southern Appalachians, from Virginia's Blue Ridge Mountains to the Monongahela National Forest of West Virginia. This book offers historical insight, outdoor adventure, and all the information most travelers need to plan and enjoy their journey. This guide also serves as an insider's handbook to the nine national parks, offering active travelers the best access points and trailheads for kayaking, biking, and hiking excursions...
Keywords: Non-Fiction; South; South Atlantic; Travel - United States